PENERAPAN TEORI BELAJAR BEHAVIORISTIK DALAM PEMBELAJARAN SHALAT - Nuralim Nuralim; Maemunah Sa’diyah; Santi Lisnawati; Abas Mansur Tamam; Imas Kurnia Rahman (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
This study aims to examine in depth the theory of behaviorisitk learning and its absorption in prayer learning. Prayer is a series of ibdah consisting of sayings and movements that in learning require practice and habituation. Therefore, researchers are interested in studying the application of this theory in prayer learning. The formulation of the problem in this research is twofold; (1) what is the concept of behavioristic learning theory and (2) how is the application of behaviristic learning theory in prayer learning? The method used in this study is a descriptive qualitative method with a library approach. Data collection techniques are carried out by examining various library sources that are relevant to research, both in the form of books and journal articles, then filtered and analyzed so as to produce a conclusion. The results of this study show that behavioristic learning theory is a learning theory that focuses on behavioral changes resulting from the relationship between stimulus and response. According to behavioristic theory with all its methods states that learning outcomes depend largely on the strength and absence of the relationship between stimulus and response. The methods of practice and repetition, habituation and rewording and paunishment developed by behaviorists are very appropriate to be applied in prayer learning.